THE SYMBOL OF THE TRINITY IN EXAMPLES OF FOLKLORE BASED SYMBOLS (Scientific journal of the Fergana State University, 2024)
The article analyzes the symbols based on the symbol of the Trinity in examples of world folklore. Psychological, structural-poetic, descriptive methods were used in the research. As a result, it was proven that the symbols, symbols, signs based on the trinity effectively embody before our eyes the various stages of the development of the socio-philosophical thinking of a certain nation from the artistic-aesthetic and philosophical aspect. It was proved on the basis of examples that the universal ideas put forward in them show their moral and educational impact for each period. The conclusions based on the scientific results of the research are the basis for the scientific and methodological addition of the theory of symbols in literary studies.